The effect of symptom frequency on the fatigue and sleep quality of adolescent cancer patients. Issue 4 (2nd October 2017) - Kudubeş, Aslı A.; Bektas, Murat; Bektas, İlknur and Selekoglu, Yasemin and Sal Altan, Sema and Ayar, Dijle
ABSTRACT: This study was performed in order to determine the effects of frequency of symptoms of adolescents with cancer on sleeping quality and fatigue. In order to collect the data, the Children Information Form, Symptom Evaluation Form, the Fatigue Assessment Scale for Pediatric Oncology Patients Between the Ages of 13 and 18 years, and the Pittsburgh Sleep Quality Index (PSQI) were used. Percentage calculations, mean, one-way variance analysis, and advanced analysis such as Scheffe tests were used. p < 0.05 was accepted as the significance. As the symptom frequencies increased in adolescents, total fatigue scale and its subdimension scores decreased and sleep quality total scores increased. There was a low relationship between the scores of symptom frequency and fatigue scale, there was a moderate association between scores of symptom frequency and the sleep quality scale scores, and there was a high relationship between the scores of fatigue ( p < 0.001). As the symptom frequencies increased in adolescents, total fatigue scale and its subdimension scores decreased and sleep quality total scores increased.